Nag Hammadi Codex VIII - Sieber, Alexander, (Nag Hammadi Studies ;, 1991)
Codex VIII from Nag Hammadi contains two tractates, Zostrianos and The Letter of Peter to Philip . This volume presents a critical edition of those texts, and includes regarding each separate text a transcription with notes, an introduction, and a translation. In addition it includes an introduction to the Codex itself, and several sets of indices. The tractate Zostrianos recounts a heavenly journey of a gnostic mystic who gains and brings back with him the saving gnosis. That gnosis is most closely related to Middle Platonism and the document intends to be part of that tradition. As such it was refuted by Plotinus and his pupil Amelius. Much of the manuscript is poorly preserved. The Letter of Peter to Philip is a gnostic revelatory discourse in letter form with Peter as its hero. The Risen Christ reveals a gnostic view of the universe and of human existence.